1971
DOI: 10.1016/0036-9748(71)90146-3
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation mobility in copper and zinc at 44°K

Abstract: The torsion technique for dislocation mobility studies in close-packed metallic crystals developed by Pope, et al. (1) was first extended to low temperatures by Gorman, et al. (Z). With this method, dislocation displacements are observed by x-ray diffraction on a crystal surface which was previously bonded directly to the torsion machine. Therefore a bonding agent must be utilized which is sufficiently strong to transmit the torsional stress pulse but pliable enough to prevent damage to the very soft test cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Further selective etch experiments in the next decades replicated these results in a vast number of materials, under different temperature ranges and under irradiation conditions [50]. Materials tested in this way include the metals W [51], Fe [44,52], Fe-C [53], Fe-Si [16,54,55], Al [56], Cu [57,58,59,60], irradiated Cu [61], Al-Cu alloys [17,21,57,62], Ni [63], Pb [64], Mg [65], Zn [66,67,68,59,69,70,71,72], Nb [73,74,75], α-Ti [76], In [77], K [52], Mo [65,78,79], Ag [80], and a number of ceramics and semiconductors, including pure Ge [81] and Si [82,83], LiF [48,84,85,86], BeO [87], KCl [88], Na...…”
Section: Experimental Evidencementioning
confidence: 94%
See 1 more Smart Citation
“…Further selective etch experiments in the next decades replicated these results in a vast number of materials, under different temperature ranges and under irradiation conditions [50]. Materials tested in this way include the metals W [51], Fe [44,52], Fe-C [53], Fe-Si [16,54,55], Al [56], Cu [57,58,59,60], irradiated Cu [61], Al-Cu alloys [17,21,57,62], Ni [63], Pb [64], Mg [65], Zn [66,67,68,59,69,70,71,72], Nb [73,74,75], α-Ti [76], In [77], K [52], Mo [65,78,79], Ag [80], and a number of ceramics and semiconductors, including pure Ge [81] and Si [82,83], LiF [48,84,85,86], BeO [87], KCl [88], Na...…”
Section: Experimental Evidencementioning
confidence: 94%
“…Further selective etch experiments in the next decades replicated these results in a vast number of materials, under different temperature ranges and under irradiation conditions [50]. Materials tested in this way include the metals W [51], Fe [44,52], Fe-C [53], Fe-Si [16,54,55], Al [56], Cu [5760], irradiated Cu [61], Al–Cu alloys [17,21,57,62], Ni [63], Pb [64], Mg [65], Zn [59,6672], Nb [7375], α -Ti [76], In [77], K [52], Mo [65,78,79], Ag [80], and a number of ceramics and semiconductors, including pure Ge [81] and Si [82,83], LiF [48,8486], BeO [87], KCl [88], NaCl [89], KBr [90,91], InSb [82,92], GaAs [93], GaSb [82], InP [94], GeSi [95,96]. In Si, particular focus was placed on studying the mobility of dislocations under various temperatures and doping conditions, often with seemingly contradictory results [82,…”
Section: Experimental Evidencementioning
confidence: 99%
“…Extensive experiments [15][16][17] have successfully captured the motion of dislocations in materials under external loading, however, current experimental investigation of dynamic behavior of an individual dislocation in metallic solids is a daunting challenge due to the angstrom-scale core structure and the characteristic THz-level frequencies of the localized lattice vibrations associated with the fast moving dislocations. Direct experimental observation of sonic dislocations in solids were not possible until an alternative material, a plasma crystal, was recently developed [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…to measure dislocation mobility in copper by Greenman,et al,and Jassby and Vreeland.3,4,5 Dislocation velocities up to about 90 m/sec were observed in these measurements, and the velocity increased linearly with resolved shear stress (up to about 1.7 M Pa). The velocity increased with decreasing temperature at constant stress, and it was concluded that phonon drag was the primary source of resistance to dislocation motion at resolved stresses areater than about 0.1 M Pa.…”
Section: S~2mentioning
confidence: 78%